Free software for libraries, its importance and use: the GNUTECA case - Damasio, Edilson (2006)
This article presents the importance of the use of softwares for libraries, having "free software", its advantages. Through the use of “Gnuteca-Sistema de Gestão de Acervo, Empréstimos e Colaboração para Bibliotecas” (Gnuteca-System of Collection Management, Lending and Collaboration for Libraries), that was developed by the Center Univ. Univates, it is being used in Brazil and other countries. It uses the methodology GNU and was developed to use MARC21 standards and to import data of Microisis. The article presents the types of softwares, the importance of softwares without costs, and the definition of free software. It has as a result of bibliographical research, the use of Gnuteca, its advantages for the libraries, its interoperability with others softwares, its main modules and its interface in the InterNet. It was demonstrated that it is a viable software for libraries that do not want to have costs with licenses of softwares.